1993
DOI: 10.1007/bf00375076
|View full text |Cite
|
Sign up to set email alerts
|

Cation specificity and pharmacological properties of the Ca2+-dependent K+ channel of rat cortical collecting ducts

Abstract: The luminal membrane of principal cells of rat cortical collecting duct (CCD) is dominated by a K+ conductance. Two different K+ channels are described for this membrane. K+ secretion probably occurs via a small-conductance Ca(2+)-independent channel. The function of the second, large-conductance Ca(2+)-dependent channel is unclear. This study examines properties of this channel to allow a comparison of this K+ channel with the macroscopic K+ conductance of the CCD and with similar K+ channels from other prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…The cholinesensitive inward current was smaller than the TTX-sensitive inward current. This may be attributed to the high concentrations of extracellular choline that have been reported to reduce voltage-gated potassium currents (Fatt and Katz, 1953;Schlatter et al, 1993;Delmas and Gola, 1995), which would cause an underestimation of the net inward current. Although the inward current was small, the choline substitution experiment is consistent with the notion that sodium currents exist in a subset of ON bipolar cells that enhance light-evoked voltage responses.…”
Section: Voltage-gated Sodium Currents Were Present In Transient On Bmentioning
confidence: 99%
“…The cholinesensitive inward current was smaller than the TTX-sensitive inward current. This may be attributed to the high concentrations of extracellular choline that have been reported to reduce voltage-gated potassium currents (Fatt and Katz, 1953;Schlatter et al, 1993;Delmas and Gola, 1995), which would cause an underestimation of the net inward current. Although the inward current was small, the choline substitution experiment is consistent with the notion that sodium currents exist in a subset of ON bipolar cells that enhance light-evoked voltage responses.…”
Section: Voltage-gated Sodium Currents Were Present In Transient On Bmentioning
confidence: 99%
“…High tubular flow rates, the consumption of diets with high-K ϩ content, and elevated aldosterone levels stimulate K ϩ secretion in the ASDN (16,24,38,53,73). K ϩ secretion within this segment is mediated by two distinct K ϩ -permeable channels: 1) renal outer medullary K ϩ channel (ROMK), a low-conductance ATP-sensitive K ϩ channel (4,19,21,25,30,76,94,103,107), and 2) BK, a high-conductance K ϩ channel that is activated by membrane depolarization, increases in intracellular Ca 2ϩ concentration, hypoosmotic stress, and membrane stretch (19,20,34,44,62,63,77,79,82,83,87). BK channels are formed by poreforming ␣-subunits and, in most cells, regulatory ␤-subunits (2,14,40,50).…”
mentioning
confidence: 99%
“…Patch-clamp studies and molecular cloning have demonstrated that ROMK-like small-conductance K (SK) channels (2-4) and big-conductance K (BK) channels (5)(6)(7)(8) are the two main types of K channels in the apical membrane of the cortical collecting duct (CCD). It is generally accepted that ROMK channels are responsible for K secretion under conditions of normal K intake because these channels have high open probability and expression (9).…”
mentioning
confidence: 99%